2019
DOI: 10.3390/medicina55010012
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Obstructive Coronary Artery Disease and Cardiac Syndrome X in Women with Typical Angina and Positive Exercise Test; Utility of Cardiovascular Risk Calculators

Abstract: Introduction: Nearly 40% of women with typical angina and a positive exercise tolerance test (ETT) have normal or near normal coronary angiography (CAG) labeled as cardiac syndrome X (CSX). Objective: We performed this study to evaluate the power of common cardiovascular risk calculators to distinguish patients with CSX from those with coronary artery disease (CAD). Methods: 559 women participated in the study. Three risk scores, including (1) newly pooled cohort equation of American College of Cardiology/Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Coronary slow flow phenomenon (CSFP) is characterized by normal/near-normal epicardial coronary arteries (stenosis < 40%) but delayed vessel opacification in the coronary angiogram (CAG) [1,2]. The prevalence of CSFP in patients undergoing CAG for suspected coronary artery disease (CAD) ranges from 1 to 7% [3].Although studies have shown that inflammation, oxidative stress, diffuse atherosclerosis, microvascular vasomotor and endothelial dysfunction are associated with CSFP [4][5][6][7][8], the exact pathogenesis of CSFP is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary slow flow phenomenon (CSFP) is characterized by normal/near-normal epicardial coronary arteries (stenosis < 40%) but delayed vessel opacification in the coronary angiogram (CAG) [1,2]. The prevalence of CSFP in patients undergoing CAG for suspected coronary artery disease (CAD) ranges from 1 to 7% [3].Although studies have shown that inflammation, oxidative stress, diffuse atherosclerosis, microvascular vasomotor and endothelial dysfunction are associated with CSFP [4][5][6][7][8], the exact pathogenesis of CSFP is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MVA, otherwise called cardiac syndrome X, is a diagnosis of exclusion that has been attributed to coronary microvascular dysfunction (CMD) by many studies. [4][5][6][7][8][9][10][11][12] Contributing factors include endothelial dysfunction, inflammation, atherosclerosis, sluggish coronary blood flow, and increased sympathetic output. It has been found that patients with endothelial dysfunction have reduced levels of endothelium-derived nitric oxide (NO) with elevated levels of endothelin-1 (ET-1), resulting in impaired local vasodilatation at capillary beds.…”
Section: Discussionmentioning
confidence: 99%
“…The patient being discussed had symptoms of typical angina with a positive ETT and a nonobstructive CAD on angiography, which are basic features needed for the diagnosis of INOCA to be made. 4-6, 8, 12 The pain of MVA is described to be generally less responsive to nitrates 4, 5 than that of obstructive CAD. It has been suggested that microvascular dysfunction is not limited to specific vascular beds.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac syndrome X (CSX) is a form of ischemic heart disease (1). Functional coronary microvascular abnormalities are often associated with endothelial dysfunction, resulting in a reduced coronary flow reserve (2,3,4). Moreover, the formation of atherosclerotic plaque inside the wall of the coronary arteries is a hallmark of coronary artery disease (CAD) which leads to the narrowing of the vessels and the clinical manifestations of the acute coronary syndrome, including angina and myocardial infarction (4,5,6).…”
Section: Introductionmentioning
confidence: 99%